Chilling Effects on Freedom of Speech and Expression in the Digital Age: A Comparative Study on the Role of the US and Indian Supreme Court (Global Journal of Human-Social Science, 2021)
The First Amendment to the United States Constitution is an essential part of the Bill of Rights The amendment prohibits making of any law respecting an establishment of religion obstructing the free exercise of religion infringing on the freedom of speech infringing on the freedom of the press interfering peoples assembling rights in a peaceful manner or prohibiting the petitioning for a governmental remedy of grievances The guarantees of this Bill of Rights were subject to the limitation imposed by the free speech and press provisions of the First Amendment to the US Constitution as interpreted and applied by the Supreme Court and other courts The United States and India are the largest democratic country and almost have similar free speech provisions in their Constitutions This Article is intended to present the free speech provisions of the American and Indian Constitution as a basic fundamental right of human being It is also to be examined that what is the role of Supreme Court in interpreting the freedom of speech and expression provisions The study also tries to incorporate the comparison between the looms of both countries as far as freedom of speech is disturbed
Keywords: freedom of speech; freedom of expression; chilling effects; comparative study; indian supreme court; us supreme court